Disparities in liver transplant waitlist characteristics and outcomes among Hispanic compared to non-Hispanic adults - Tincopa, Monica; Pace, Jordan L.; Delebecque, Fanny; Torosian, Kelly; Arellano, Denya; Martinez, Maria Elena; Vodkin, Irine; Ajmera, Veeral (Frontiers in Transplantation, 2025)
BackgroundSocial determinants of health (SDOH) and transplant center characteristics have been associated with access to liver transplantation (LT) for Hispanic individuals. The aim of this study was to identify waitlist characteristics and correlates of odds of LT and waitlist removal by Hispanic ethnicity.MethodsThis was a single-center cohort study of adults listed for LT between January 2018–December 2020. Demographic, clinical, and SDOH were analyzed using logistic regression.Results375 patients were included. 52.5% (N = 197) were Hispanic. At time of listing, Hispanic patients had significantly higher BMI, prevalence of diabetes and metabolic dysfunction associated steatohepatitis. Rates of substance use were significantly lower and time of last drink to listing was significantly longer (641 vs. 391 days, p = 0.0007) in Hispanic adults. Rates of LT and waitlist removal did not significantly differ by Hispanic ethnicity (46.9% vs. 46.1% and 35% vs. 36.5%, respectively). Hepatocellular carcinoma (OR 3.28) was associated with odds of LT whereas employment status predicted waitlist removal.ConclusionsDistribution on the waitlist, LT and waitlist removal did not differ by Hispanic ethnicity. Hispanic patients had significantly longer time from last drink to listing, suggesting referral bias. Public health interventions to optimize LT referral are needed to increase health equity.